2022
DOI: 10.1055/a-1844-0549
|View full text |Cite
|
Sign up to set email alerts
|

Leberchirurgie 4.0 - OP-Planung, Volumetrie, Navigation und Virtuelle Realität

Abstract: ZusammenfassungDurch die Optimierung der konservativen Behandlung, die Verbesserung der bildgebenden Verfahren und die Weiterentwicklung der Operationstechniken haben sich das operative Spektrum sowie der Maßstab für die Resektabilität in Bezug auf die Leberchirurgie in den letzten Jahrzehnten deutlich verändert.Dank zahlreicher technischer Entwicklungen, insbesondere der 3-dimensionalen Segmentierung, kann heutzutage die präoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Xiao et al [2] have proposed a lung nodule segmentation method based on computed tomography (CT) images for the early diagnosis of lung cancer where the recall rate of lung nodule detection reaches 99.1%. Alirr et al [3,4] have reported the application of 3D medical image segmentation to liver surgery, where the segmentation of liver, tumours and blood vessels have been done to determine the spatial relationship of the liver and calculate the required resection planning parameters. However, because of the variations in texture and shape of tumours among different individuals, the possible occurrence of the multiple tumours and their blurry boundaries, the efficient and accurate tumour segmentation is a highly challenging task.…”
Section: Introductionmentioning
confidence: 99%
“…Xiao et al [2] have proposed a lung nodule segmentation method based on computed tomography (CT) images for the early diagnosis of lung cancer where the recall rate of lung nodule detection reaches 99.1%. Alirr et al [3,4] have reported the application of 3D medical image segmentation to liver surgery, where the segmentation of liver, tumours and blood vessels have been done to determine the spatial relationship of the liver and calculate the required resection planning parameters. However, because of the variations in texture and shape of tumours among different individuals, the possible occurrence of the multiple tumours and their blurry boundaries, the efficient and accurate tumour segmentation is a highly challenging task.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, virtual reality (VR) head–mounted displays (HMD) have been introduced in various fields of medicine, such as the planning of liver surgery. 8 VR-HMDs have the advantage of allowing the participant to be completely immersed in the simulated situation and are ideal as point-of-care diagnostics due to their small size. In this study, we therefore aimed to develop an easily applicable point-of-care driving test with a focus on the reaction time to hazardous events based on VR, test its feasibility in patients with cirrhosis, and compare results between patients with cirrhosis and noncirrhotic controls.…”
Section: Introductionmentioning
confidence: 99%